2017
DOI: 10.4103/jpbs.jpbs_145_17
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders and mental health-related issues as occupational hazards among dental practitioners in Salem city: A cross-sectional study

Abstract: Background:Like in any other profession, dental surgeons are also afflicted by many occupational health hazards such as Musculoskeletal disorders (MSD) and mental health related issues.Aims:To assess the distribution of MSD and mental health related issues amidst dentists in Salem City according to age, sex and number of working hours per week.Objectives:A survey was organized to check the rate of occurrence of these occupational health hazards among dental practitioners in Salem city.Materials and Methods:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
7
0
4
Order By: Relevance
“…The 12-month prevalence of MSDs in the hand varies between 25.0% and 49.7% [ 4 , 9 , 11 13 , 18 20 ]. Other international studies report hand complaints ranging from 8.4% to 66.7% [ 8 , 14 , 15 , 21 24 ]. Other research showed that 19.2% to 50.0% of dental students develop MSDs on the hand during their studies [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 12-month prevalence of MSDs in the hand varies between 25.0% and 49.7% [ 4 , 9 , 11 13 , 18 20 ]. Other international studies report hand complaints ranging from 8.4% to 66.7% [ 8 , 14 , 15 , 21 24 ]. Other research showed that 19.2% to 50.0% of dental students develop MSDs on the hand during their studies [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 A prática odontológica pode desencadear efeitos nocivos para os profissionais, designados como riscos ocupacionais para a saúde. 4 Cirurgiõesdentistas são um grupo de risco maior devido a diversos problemas presentes no contexto ocupacional, como a postura durante a atividade clínica. 2,5 Os profissionais estão expostos a uma série de perigos físicos, mecânicos e químicos, causadores de várias doenças específicas, que se desenvolvem e se intensificam com os anos.…”
Section: Introductionunclassified
“…2,5 Os profissionais estão expostos a uma série de perigos físicos, mecânicos e químicos, causadores de várias doenças específicas, que se desenvolvem e se intensificam com os anos. 4,6 A odontologia é uma profissão que demanda atenção e precisão nos movimentos realizados, e o profissional deve constantemente interagir com ferramentas e equipamentos para realizar o atend i mento. A s si m , é n at u r a l que s e aumente a tensão muscular com o decorrer das horas trabalhadas.…”
Section: Introductionunclassified
See 2 more Smart Citations